A critique of climate damage modeling: Carbon fertilization, adaptation, and the limits of FUND. (February 2016) - Ackerman, Frank; Munitz, Charles
Abstract: Among the climate economics models widely used in policy analysis, FUND is unique in several respects, including its disaggregated, modular treatment of damages and its relatively low estimates of damages and the social cost of carbon (SCC). We present two possible reasons for FUND's low damage estimates: the representation of carbon fertilization in agriculture; and assumptions about the extent of adaptation. We explore these issues in FUND 3.8, comparing the model's default results to scenarios without carbon fertilization and adaptation. We find that carbon fertilization is projected to provide a large net benefit, offsetting many of the damages in other categories; almost half of this benefit occurs in China, based on FUND's assumptions about the regional strength of carbon fertilization. Automatic adaptation, tied to increases in per capita income, reduces many damages, particularly deaths caused by climate change; almost three-fourths of the reduction in climate-linked deaths is projected to occur in sub-Saharan Africa. Moreover, many categories of damages are surprisingly small, a topic that warrants further research. As long as FUND's default forecasts remain significant in climate policy debate, it is important to understand the sources of FUND's low estimates of climate damages.